Scanning Lidar Measurements of the Full-Scale RDD Field Trial Puff Plumes. Issue 5 (May 2016) - Cao, Xiaoying; Roy, Gilles
Abstract : Abstract: A vertically scanning lidar (light/radar) was used to measure the time evolution of clouds generated by a small explosive device. Vertical sweeps were performed at a downwind distance of 105 m from the detonation. The measured quantity obtained from the lidar was the light extinction coefficient. This quantity is directly proportional to the aerosol concentration. The background aerosol value was set to 0.0001 m −1 (assuming a visibility of 40 km), and assuming the scattering properties of the explosively generated cloud is the same as the background aerosol, the authors found that the instantaneous maximal local concentration of aerosol in the cloud did not exceed 500 times the background aerosol value, and the instantaneous concentration was typically less than five times the background aerosol value. In the two trials that were done, the volumes of the clouds were reasonably close at 2, 700 m 3 and 4, 000 m 3, respectively.